A genetic basis for atrophy: dominant non-responsiveness and helicobacter induced gastritis in F1 hybrid mice. Issue 3 (1st September 1999) - Sutton, P; Wilson, J; Genta, R; Torrey, D; Savinainen, A; Pappo, J; Lee, A
Abstract : BACKGROUND: The importance of host factors in helicobacter induced gastritis has been shown in animal models. Infection of most mouse strains with Helicobacter felis results in a functional atrophic gastritis, while other strains remain gastritis free. AIMS: To investigate these host factors further by using genetic crosses of responder and non-responder mice. METHODS: F1 hybrids of the non-responder CBA/Ca strain and three strains of mice known to develop H felis induced gastritis were infected for three months with H felis . Gastritis was assessed by histopathology and serum antibody responses by ELISA. RESULTS: Infection of CBA/Ca mice and F1 hybrids induced little or no gastritis. Analyses of the antibody responses in these mice revealed virtually undetectable anti-helicobacter antibody levels despite colonisation with high numbers of H felis . In contrast, infection of H felis responsive strains induced gastritis and a significant humoral immune response. CONCLUSIONS: The non-responsiveness of CBA/Ca mice to H felis infection is dominantly inherited. The lack of gastritis in CBA mice and their offspring is probably due to active suppression of the immune response normally mounted against H felis . Investigation of these mechanisms will provide important insights relevant to induction of gastric atrophy and cancer in humans.